2020
DOI: 10.21203/rs.3.rs-109862/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perioperative mortality of head and neck cancers

Abstract: Background: Head and neck cancers are aggressive cancers, most clinical studies focused on the prognosis of patients with head and neck cancer. However, perioperative mortality was few mentioned.Methods: A retrospective analysis was performed using all head and neck cancer patients admitting in the Department of Oral and Maxillofacial Surgery of the Second Xiangya Hospital, Central South University from January 2010 to December 2019. The analysis of overall survival and progression-free survival were performed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…SSI can prolong hospital stays, increase medical costs and, in severe cases, even lead to death [2,8]. Our previous studies have shown that SSI is associated with increased perioperative mortality and poorer OS in HNC patients [9]. In this study, we found that SSI increased the ap failure rate and the length of postoperative hospital stay.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…SSI can prolong hospital stays, increase medical costs and, in severe cases, even lead to death [2,8]. Our previous studies have shown that SSI is associated with increased perioperative mortality and poorer OS in HNC patients [9]. In this study, we found that SSI increased the ap failure rate and the length of postoperative hospital stay.…”
Section: Discussionsupporting
confidence: 53%
“…Meanwhile, SSI increases the mortality during the perioperative period. In our previous study we found that SSI is a risk factor for perioperative death of HNC and it is signi cantly correlated with poor overall survival (OS) of HNC patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…[2,8]. Our previous studies have shown that SSI is associated with increased perioperative mortality and poorer OS in HNC patients [9]. In this study, we found that SSI increased the ap failure rate and the length of postoperative hospital stay.…”
Section: Multivariate Logistic Regression Analysis Of Risk Factors Of Ssi In Hnc Patientssupporting
confidence: 58%
“…Meanwhile, SSI increases the mortality during the perioperative period. In our previous study we found that SSI is a risk factor for perioperative death of HNC and it is signi cantly correlated with poor overall survival (OS) of HNC patients [9]. The patients' data was collected and sorted from our hospital's electronic database, which contains prior medical records and postoperative follow-up information.…”
Section: Introductionmentioning
confidence: 99%
“…HNC-specific reasons can be rupture of large vessels in advanced disease. Cardiovascular or respiratory failure is other frequent reasons, mainly attributed to the severe comorbidity of the patients [22]. Second, this study was retrospective, which could lead to misclassification error and unmeasured variables.…”
Section: Discussionmentioning
confidence: 98%